Silver Nitrate Catalyzed Sulfonylation of O-Propargyl Alkynes - Sátiro, Bárbara G.; Moura, Igor M. R.; Almeida, Cláudia L. A.; Freitas, Queila P. B.; Oliveira, Roberta A.; Menezes, Paulo H. (Synlett, 2023)
The development of new catalytic methods based on lower-cost metals under environmentally friendly conditions is still a challenge. Herein, we report an efficient strategy for the synthesis of vinyl sulfones from O-propargyl alkynes and sodium salts of sulfinic acids using silver nitrate, an inexpensive and readily available catalyst, under air atmosphere using aqueous conditions. The products were obtained in good to moderate yields, and the mechanism of the reaction was also investigated.
Keywords: vinyl sulfones; sodium organosulfinates; silver catalysis; alkynes; sulfonylation